Neuroplasticity and Epilepsy Surgery in Brain Eloquent Areas: Case Report - Serrano-Castro, Pedro Jesus; Ros-López, Bienvenido; Fernández-Sánchez, Victoria Eugenia; García-Casares, Natalia; Muñoz-Becerra, Luis; Cabezudo-Garcia, Pablo; Aguilar-Castillo, Maria José; Vidal-Denis, Maria; Cruz-Andreotti, Esperanza; Postigo-Pozo, Maria Jose; Estivill-Torrús, Guillermo; Ibañez-Botella, Guillermo (Frontiers in Neurology, 2020)
INTRODUCTION: Neuronal plasticity includes changes in any component of the central nervous system in response to intrinsic or extrinsic stimuli. Brain functions that depend on the epileptogenic cortex pose a challenge in epilepsy surgery because many patients are excluded from presurgical evaluation for fear of the possible sequelae. Some of these patients may be rescued by enhancing neuronal plasticity with brain neuromodulation techniques. CASE REPORT: We describe a 6-year-old child with refractory focal motor seizures symptomatic to a neuroepithelial dysembryoblastic tumor in the left temporo-parietal region. He underwent limited resection of the lesion in order to avoid sequelae in his language function. A functional study at age of 17 years revealed an overlap of Wernicke’s area with the tumor and areas of incipient language reorganization in the contralateral hemisphere. An invasive neuromodulation procedure was designed to enhance neuroplasticity. After craniotomy, he underwent language training and simultaneous electrical inhibition of language using an electrode grid placed over the lesion. The intensity of the language inhibitory stimulus was increased every day to force the use of accessory language areas in the right hemisphere by neuroplasticity. RESULTS: The language of the patient improved for six consecutive days until he was able to speak and understand while undergoing maximum electrical inhibition. The tumor was resected using a cortical mapping guide. DISCUSSION: Application of direct cortical stimulation techniques and language prehabilitation before epilepsy surgery can be useful to rescue patients excluded from resective surgery, especially young patients with long-term lesions.